Environmental Health Management and Prevention Practices - Makan, Abdelhadi (IntechOpen, 2020)
It took a long time for humans to recognize the existence of a direct link between environmental pollution and health deterioration. In the 1990s, scientists demonstrated the existence of this link through epidemiological studies and new technical materials that can measure accumulation effects of small toxic quantities. Consequently, concerns about human health were accentuated, and the notion of environmental health has emerged. This book covers some practices for managing, controlling, and preventing environmental factors that may affect current and future generations' health. Topics relate to either the natural or the built environment and include air and water pollution, rainwater harvesting, climate change effects, marine pollution, and ecological indicators.